Mechanistic insights into PROS1 inhibition of bladder cancer progression and angiogenesis via the AKT/GSK3β/β-catenin pathway - Xin-peng Fan; Ji-rong Wang; Si-yu Chen; Xiao-ran Li; Jin-long Cao; Hua-bin Wang; Li-yun Ding; Tuan-jie Che; Li Yang (Scientific Reports)
Abstract Bladder cancer (BLCA) is one of the ten most common cancers worldwide. However, the deregulation of PROS1 and its specific function in BLCA is not well understood. By combining proteomic and transcriptomic datasets, we discovered PROS1 expression was significantly reduced in BLCA tissues and revealed the clinical relevance of PROS1 with BLCA. Analysis of multiple BLCA datasets consistently showed the group with reduced PROS1 expression was linked to cancer-promoting pathways, more aggressive characteristics, and a greater chance of responding positively to immunotherapy. Next, various functional experiments were performed and the results revealed PROS1 overexpression inhibited the proliferation, cell cycle progression, migration, invasion, and angiogenesis of BLCA. In recovery trials, the AKT activator SC79 offered additional proof that PROS1 may influence BLCA cells via the AKT/GSK3β/β-catenin pathway. In conclusion, as an angiogenesis-related gene, PROS1 may play an inhibitory role in the biological functions of bladder cancer.